Chronic pancreatitis. Issue 5 (September 2017) - Yang, Dennis; Forsmark, Chris E.
Abstract : Purpose of review: Summarize key clinical advances in chronic pancreatitis reported in 2016. Recent findings: Early diagnosis of chronic pancreatitis remains elusive. Recent studies suggest that endoscopic ultrasound may be less accurate than previously thought and new MRI techniques may be helpful. Genetic predisposition may independently affect the clinical course of chronic pancreatitis and the risk for pancreatic cancer. Cigarette smoking may have a greater negative impact on chronic pancreatitis than previously thought and moderate alcohol consumption may be protective. A multidisciplinary approach is necessary for the treatment of type 3 diabetes and nutritional deficiencies in chronic pancreatitis. Although endoscopic therapy remains a reasonable first-line option in treating chronic pancreatitis and its complications, early surgical intervention may be indicated for pain in select patients. Summary: Newer endoscopic ultrasound and MRI techniques are being evaluated to help with the early diagnosis of chronic pancreatitis. Both genetic predisposition and cigarette smoking are increasingly recognized as having a major impact in the course of the disease and the risk for pancreatic cancer. Endoscopic therapy is well tolerated and effective for the treatment of chronic pancreatitis and its complications although an early surgical approach for pain may be associated with improved clinical outcomes.